Laryngeal adenosquamous carcinoma: A population‐based perspective. (9th October 2015) - Dubal, Pariket M.; Unsal, Aykut A.; Echanique, Kristen A.; Vazquez, Alejandro; Reder, Lindsay S.; Baredes, Soly; Eloy, Jean Anderson
Abstract : Objectives/Hypothesis: Adenosquamous carcinoma (ASC) is a rare entity, with fewer than 100 cases having been reported in the upper aerodigestive tract. Thus, no large samples characterizing its clinical behavior are available in the literature. Investigation of ASC has been further limited by difficulty in establishing histopathologic diagnosis. Our objective was to use a national population‐based resource to evaluate patient demographics, clinical behavior, incidence, and survival for laryngeal adenosquamous carcinoma (LASC). Study Design: Retrospective population‐based analysis. Methods: The National Cancer Institute's Surveillance, Epidemiology, and End Results database was used to search for patients diagnosed with LASC between 1973 and 2012. Patient demographics, tumor characteristics, incidence, and survival trends were analyzed. Results: Of the 68 identified LASC patients, 79.4% were male and 20.6% were female. The mean age at diagnosis was 66.0 ± 10.8 years. Whites represented 80.9% of patients, but no racial predominance was noted. LASC most commonly affected the glottis (47.1%), followed closely by the supraglottis (42.6%). Most cases were poorly differentiated (59.2%) and presented with stage IV disease (40.7%). Metastasis (M1) was noted in 10.7% of cases. The overall incidence was 0.003/100, 000. The 5‐year disease‐specific survival rate was 36.6%, with a median observed survival of 33.6 months. Conclusions: This study notes that LASC has low overall incidence. It has a predilection for males, but does not demonstrate racial predominance. LASC tends to present with stage IV disease, with distant metastasis noted in approximately one in 10 cases. Overall prognosis is poor, with a median survival under 3 years. Level of Evidence: 4 Laryngoscope, 126:858–863, 2016